Manipulating the baby biome: What are the issues?. (22nd March 2017) - Lee, Lai‐yang; Garland, Suzanne M.; Giles, Michelle L.; Daley, Andrew J.
Abstract : Establishing a baby biome through the controversial practice of 'vaginal seeding' has generated interest among the general public and healthcare providers alike. We discuss the potential risks of this practice and offer a harm minimisation approach to managing women requesting vaginal microbiome transfer after delivery by caesarean section.